Unwind - Book 1 - Shusterman, Neal. (New York : Simon & Schuster Books for Young Readers, 2007)
In a future world where those between the ages of thirteen and eighteen can have their lives "unwound" and their body parts harvested for use by others, three teens go to extreme lengths to uphold their beliefs--and, perhaps, save their own lives.
HL740L
Accelerated Reader AR
Keywords: Fugitives from justice; Juvenile fiction; Survival; Juvenile fiction; Revolutionaries; Juvenile fiction; Fugitives from justice; Fiction; Survival; Fiction; Revolutionaries; Fiction